Retirement expectations, pension reforms, and their impact on private wealth accumulation - Renata Bottazzi; Tullio Jappelli; Mario Padula (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
We estimate the effect of pension reforms on households' expectations of retirement outcomes and private wealth accumulation decisions exploiting a decade of intense Italian pension reforms as a source of exogenous variation in expected pension wealth. The Survey of Household Income and Wealth, a large random sample of the Italian population, elicits expectations of the age at which workers expect to retire and of the ratio of pension benefits to pre-retirement income between 1989 and 2002. We find that workers have revised expectations in the direction suggested by the reform and that there is substantial offset between private wealth and perceived pension wealth, particularly by workers that are better informed about their pension wealth.
urn:nbn:de:hebis:30-26018
Keywords: E21; H55; 330; Expectations; Pension Reform; Rentenreform; Erwartungstheorie; Alterssicherung; Haushaltseinkommen; Italien